Dysregulatory Changes in the Lymphocytic Antiradical Defense System in Severe Concomitant Brain Injury - T. F. Sokolova; V. T. Dolgikh; T. I. Dolgikh; Yu. V. Yemelyanov; N. Ye. Turok (Общая реаниматология)
Objective: to reveal the mechanisms of changes in the antioxidative defense system of the lymphocytes, spleen and thy-mus in severe brain injury.Materials and methods. Experimental studies were performed on 257 nembutal (40 mg/kg)-anesthetized noninbred male albino rats weighing 200—230 g. Severe mechanical injury was simulated by the Noble-Collip procedure. The activity of superoxide dismutase, catalase, glucose-6-phosphate dehydrogenase, and glutathione reductase and the level of reduced glutathione were determined in the peripheral blood lymphocytes, spleen, and thymus within 30 posttraumatic days.Conclusion. The specific features of changes have been revealed in the activity of antioxidative enzymes in the lymphocytes and organs of immunogenesis: there is a preponderance of discoordination in the antiperox-ide system of peripheral lymphocytes and in the antioxidative defense system of lymphoid organs. The posttraumatic inactivation of the enzymes is associated with their baseline levels: the higher activity of an enzyme is seen in the lymphocytes of a healthy organism and accordingly its implication in the inactivation of excess products of free radicals, the more significant reduction is in its activity in injury. The abnormal changes in the metabolic resource of the lymphocytic antioxidative system, occurring in the early stages of traumatic disease, persisted within 3 weeks and they tended to normalize only by day 30. The impaired enzymatic activity in the lymphoid cell antiradical and antiperoxide defense accounts for the diminished functional capacities of the immune system in the posttraumatic period. The duration of inhibited activity of antioxidative enzymes, which determines the rate of lipid peroxidation processes of lymphocytes and immunogenesis organs, induces prolonged immunodeficiency in the posttraumatic period.